(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Microdebrider-assisted turbinoplasty of inferior turbinate is a surgical procedure for reducing the size of turbinate and achieve patent nasal airways in a condition where an enlarged turbinate cause chronic nasal obstruction not responding to medical treatment. Objective:To assess the results of microdebrider technique in the management of patients with chronic nasal obstruction due to inferior turbinate hypertrophy. Methods: From January 2010 to March 2011, forty patients with chronic nasal obstruction due to inferior turbinate hypertrophy not responding to medical treatment were treated with microdebrider-assisted turbinoplasty. They were subjected to detailed study of medical history and clinical examination. Post-operative follow up was performed for subjective and objective evaluation up to one year. Results:Thirty seven patients (92.5 %) had good airway passage during the first two weeks after operation and these results continued up to twelve months. The complications encountered with this procedure were limited to postoperative bleeding with no crusting or adhesions. Conclusion: Microdebrider-assisted turbinoplasty is a safe procedure for achieving turbinate size reduction with acceptable morbidity in patients with nasal obstruction due to turbinate hypertrophy. Bleeding is a minimal complication. Preservation of mucosa leads to early healing and absence of crusting. Keywords: Turbinate, partial turbinectomy, microdebrider